INVESTIGATION OF ABILITY OF TUBERCULOUS MYCOBACTERIA TO MULTIPLY IN ALVEOLAR MACROPHAGES OF THE PATIENTS AFTER THE COURSE OF ANTI-TUBERCULOSIS TREATMENT - E. G. Ufimtseva; N. I. Eremeeva; D. V. Vakhrusheva; S. N. Skornyakov (Туберкулез и болезни лёгких)
.